FRI0423 Impact of Disease Activity on Organ Damage Risk Over Time in Systemic Lupus Erythematosus – The Hopkins Lupus Cohort. (9th June 2015) - Burge, R.T.; Al Sawah, S.; Zhang, X.; Wang, Y.; Magder, L.; Petri, M.
Abstract : Background: Disease activity increases the risk of irreversible organ damage in systemic lupus erythematosus (SLE), but estimating that risk in absolute terms is challenging, given disease activity fluctuations, variable disease durations, and the roles of comorbid factors and treatment (corticosteroids) in organ damage. Objectives: To understand the impact of disease activity (measured by SELENA-SLEDAI score) and proportion of time with a certain level of disease activity (measured by the proportion of clinic visits with disease activity at or above a prespecified SELENA-SLEDAI score) on the risk of developing new irreversible organ damage, as measured by the SLICC/ACR Damage Index (SDI) score. Methods: Cox proportional hazard models were used to estimate the impact of predictors, including measures of disease activity as time-dependent variables, on the risk of developing any new organ damage over time. Results: Patients (N=2199) were followed for an average of 6.2 years (mean age at cohort entry, 38.0 years; mean disease duration, 5.1 years). The most frequent types of organ damage occurring over time were ocular (cataract) and musculoskeletal (osteoporotic fractures). In an initial model excluding the variable "proportion of clinic visits with SLEDAI score ≥6", age and SDI score at cohort entry, SLEDAI score (<6 vs. ≥6) during follow-up, and corticosteroid use (<7.5mg/dl vs ≥7.5 mg/day) during follow-up were significant predictors of the risk of developing any new organ damage (Model 1). When including the "proportion of clinic visits with SLEDAI score ≥6" (Model 2), SLEDAI score (<6 vs. ≥6) during follow-up was no longer significant. For Model 3, we excluded the time-dependent variable "SLEDAI score (<6 vs. ≥6) during follow-up" from the model, and the effect of "proportion of clinic visits with SLEDAI score ≥6" was slightly reduced but remained significant. Conclusions: Organ damage in SLE is multifactorial, with both corticosteroid treatment and disease activity playing roles. However, patients with high levels of disease activity for a greater proportion of the follow-up time had significantly higher organ damage risk compared to those with high levels of disease activity for a lesser proportion of the follow-up time. These findings call for active measures to control disease activity over time in SLE. Disclosure of Interest: R. Burge Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. Al Sawah Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, X. Zhang Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Y. Wang Consultant for: Eli Lilly and Company, Employee of: inVentiv Health Clinical, L. Magder: None declared, M. Petri: None declared